Relationship Of Maternal Nutrition Status And Mother's Height Of Stunting Events In Tolls At Puskesmas Pagambiran - Annisa Namirah Nasution; Vaulinne Basyir; Rinang Mariko; Nur Afrainin Syah; Yusri Diannne Jurnalis; Hudila Rifa Karmia (Universitas Islam Negeri Sumatera Utara, Medan, 2023)
Abstract Stunting is a chronic malnutrition problem characterized by height for age which is <-2 SD according to the median standard of child growth. Stunting causes poor quality of human resources, which will reduce productivity. The factor causing the problem of stunting In Tools AtPagambiran Health Center, Padang City is the lack of clean water sanitation. The purpose of this study was to determine the relationship between the nutritional status of the mother, the height of the mother, and the mother's knowledge of the incidence of stunting in toddlers at the Pagambiran Health Center, Padang City.This research is an observational analytic study with a cross-sectional design. This research was conducted at the Pagambiran Health Center in Padang City with 3457 populations in November 2021-December 2022. The research sample was 174 mothers and children aged 24-59 months. Sampling using Stratified Random Sampling and Simple Random Sampling. Data collection used a questionnaire and the MCH handbook. The statistical tests used are Chi-square and Logistic Regression.The results of the univariate study found that 55 mothers (31.6%) had a history of chronic energy deficiency, and 12 mothers (6.9%) had a height < 150 cm. The results of the bivariate study using chi-square analysis obtained the p-value of each variable, namely the mother's nutritional status (p=0.005) and mother's height (p=0.018). The study concludes that there is a relationship between the mother's nutritional status and the mother's height in the incidence of stunting in toddlers at the Pagambiran Health Center, Padang City. Researchers suggest that counseling related to stunting can be carried out for pregnant women and prospective brides as an initial preventive measure. Keywords: Chronic Energy Deficiency, Mother's Height, Stunting.